Kidney Transplantation in Elderly Recipients: Five-Year Experience - Paulo, Núria; Fernandes, Vítor; Cerqueira, Ana; Bustorff, Manuela; Pinho, Ana; Sampaio, Susana; Pestana, Manuel (Brazilian Journal of Transplantation, 2024)
Objectives: The prevalence of end-stage renal disease is rising among older adults worldwide. Despite kidney transplantation being considered the best renal replacement therapy, it presents unique challenges in elderly patients. This study aims to describe deceased donor kidney transplantation in our center, analyze outcomes namely delayed graft function (DGF), acute rejection, bacterial infections, and death-censored allograft loss in patients aged 65 years or older, and compare graft and patient survival with recipients younger than 65 years old. Methods: A single-center retrospective cohort study of kidney transplantation from a deceased donor between 2016 and 2020 was conducted. Data on donor, recipient, and transplant characteristics were collected, and outcomes after transplantation were analyzed. Univariate Cox regression was used to compare patient and death-censored allograft survival between older and younger patients. Results: Of the 294 deceased-donor transplants performed, 48 were allocated to recipients aged 65 years or older. These patients had a significantly higher prevalence of extended criteria donors (ECD) when compared to younger recipients (p < 0.001). The mean recipient age in the elderly group was 68 ± 2 years, with a median follow-up of 29 months (interquartile range [IQR]18-49). During the 1st year, five (10.4%) patients were diagnosed with biopsy-proven acute rejection and 24 (50%) with bacterial infections. DGF was observed in 27 (56.3%) patients and was associated with a higher proportion of high-risk donors (ECD and uncontrolled circulatory death donors with normothermic regional perfusion) (p = 0.034), longer cold ischemic times (p = 0.031), and hospitalization duration (p < 0.001). Death-censored allograft survival at 1, 3, and 5 years was 89.1, 89.1, and 84.6%, respectively, which was not statistically different from the group of younger recipients (p = 0.56). Throughout follow-up, five patients died, three (60%) of whom had a functioning allograft. Patient survival at 1, 3, and 5 years was 100, 97.6, and 79.2%, respectively, again showing no notable differences compared to younger recipients (p = 0.12). Conclusion: Even though an individualized approach and careful pre-transplant evaluation are key for the success of kidney transplantation in the elderly population, our 1, 3, and 5-year death-censored allograft and patient survival in older patients were similar to younger recipients.